2014
DOI: 10.2298/tsci111212163k
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of melting of nano-enhanced phase change material in latent heat thermal energy storage system

Abstract: The heat transfer enhancement in the latent heat thermal energy storage system through dispersion of nanoparticle is reported. The resulting nanoparticleenhanced phase change materials exhibit enhanced thermal conductivity in comparison to the base material.Calculation is performed for nanoparticle volume fraction from 0 to 0.08. In this study rectangular and cylindrical containers are modeled numerically and the effect of containers dimensions and nanoparticle volume fraction are studied. It has been found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…During discharging where the copper has transferred maximum heat to the HTF and ended up at 44 °C in 190 minutes and the similar data for brass and aluminum are 70 °C in 150 minutes and 65 °C in 190 minutes, respectively. Obviously, the charging is earlier than the discharging because of solid boundary formation during solidification of PCM during discharging which prevents heat transfer in the storage system [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…During discharging where the copper has transferred maximum heat to the HTF and ended up at 44 °C in 190 minutes and the similar data for brass and aluminum are 70 °C in 150 minutes and 65 °C in 190 minutes, respectively. Obviously, the charging is earlier than the discharging because of solid boundary formation during solidification of PCM during discharging which prevents heat transfer in the storage system [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…The effective properties of nanofliuid such as density, heat capacity, etc., are modeled with a following simple relation [11,20]:…”
Section: Governing Equationsmentioning
confidence: 99%
“…In this paper, gas release and pressure increase during the solidification was neglected. Also, the latent heat of nanofluid is modeled as [11,20]:…”
Section: Governing Equationsmentioning
confidence: 99%
“…The results showed that the melting time of a PCM depends on geometric parameters, thermal parameters and thermo-physical properties of the PCM. Kashani et al [4] numerically studied the performance of heat transfer of PCM with different concentrations of copper nanoparticles in rectangular and cylindrical enclosures. The results showed that the cylindrical container of the same nano-PCM takes two times longer period than rectangular container.…”
Section: Introductionmentioning
confidence: 99%